LEGAL BARRIERS AND POLICY GAPS IN INDUSTRIAL SYMBIOSIS: A PATHWAY TO REGULATORY INNOVATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The latest report on the Circularity gap reveals that the circularity ratio in 2022 has dropped by 21%. Simultaneously, in just the past six years alone, global consumption reached over half a trillion tonnes of materials - nearly as much as the entirety of the 20th century. This paper explores the key legal and policy facilitators and barriers that prevent businesses from fully engaging in Industrial Symbiosis, focusing on EU waste legislation and national regulatory constraints, applying methodologies such as literature review and analysis of secondary data. This research aims to analyse policy planning documents and identify key strategies for implementing Industrial Symbiosis. The paper highlights practical solutions to support the expansion of Industrial Symbiosis by addressing the legal and policy roadblocks. Overcoming these barriers will help businesses operate more sustainably, foster cross-sector collaboration, and accelerate the shift toward a circular and resource-efficient economy. In addition, the implementation of Industrial Symbiosis will also lead to the country’s ability to i) account for credible and verifiable data for waste prevention, ii) increase resource productivity rate (which is currently a significant issue for countries such as Latvia), iii) increase material circularity rate. The main findings and conclusions will outline the strategies required at the policy and regulatory levels to foster industrial symbiosis. The paper provides practical recommendations to policy planners on how to apply Industrial Symbiosis for an efficient country’s economy’s transition to a circular economy.